Digital Zakat Governance for Accelarating Zakat Growth - Rahmini Hadi; Sri Malika Sari; Alizar Isna; Tri Meliana Rahmatika Putri (CV. Sakura Digital Nusantara, 2026)
Purpose - This policy-oriented integrative conceptual review develops a framework explaining how digital access, data integrity, reporting transparency, and voluntary zakat payroll can support sustainable formal zakat growth in Indonesia. Design/methodology/approach - This policy-oriented integrative conceptual review audits 32 traceable records: 27 scholarly sources, three official BAZNAS reports, and two method sources. Google Scholar served only as a relevance-ranked discovery layer, not as a structured database or basis for completeness claims. Original page, candidate, and full-text exclusion counts were not retained, so no screening denominator was reconstructed. All retained records were reverified through exact-title searches, DOI metadata, publisher or journal pages, DOAJ, accessible full text, or official repositories. Directed content analysis coded 30 substantive sources. Findings/Results - The Technology Acceptance Model explains digital adoption. Digital transformation theory explains process and data integration. Agency theory and public accountability explain how data integrity and disclosure support trust. Compliance theory explains voluntary payroll continuity. Systems theory integrates the pathways through institutional accountability. Cybersecurity, digital inclusion, amil capability, interoperability, leadership, audit quality, sharia compliance, and ethical consent act as boundary conditions. Originality/value - The framework operationalizes data integrity across transaction, muzaki, payroll, fund-classification, distribution, reconciliation, security, and audit-trail records. It formulates five testable propositions, aligns each proposition with its mediator and outcome, and separates zakat-specific collection from wider ZIS-DSKL and off-balance-sheet reporting.